Technology usage in time of COVID-19 pandemic among university students: a descriptive study - Md Noh, Nur Hidayah; Abu Bakar, Nurul Syahida; Sa’at, Nadiah; Ahmad, Aimi Athirah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
The world is going through a difficult time due to the presence of COVID-19 pandemic. The pandemic has necessitated the use of online, virtual classrooms in place of face-to-face ones. This raises concerns about students' ability to adjust to the transition to online learning, considering their diverse socioeconomic backgrounds. Thus, it is critical to assess students' experiences with technology adoption in the current learning environment during a pandemic. The purpose of this study is to elicit information about students' experiences with gadgets, internet access, online tools, online class engagement, and online learning material during open and distance learning in times of pandemic COVID -19 via the crosstabulation analysis. This study involved students from two universities and three levels of study: foundation, diploma, and bachelor. Most foundation students were living in campus while most diploma and degree students were living off campus. This situation affects the experience faced by students in online learning in terms of their engagement, ease of using online tools and how they access materials. This study suggests that with good internet connectivity, students' satisfaction with online learning may rise when they can easily access all course materials, rewatch online lectures and become actively engaged with learning materials without lag. Thus, sustaining the quality of online education requires a strong internet connection that will lead to students satisfactory in online learning especially to those who are remotely learning online from home.